UPAYA PENINGKATKAN KEMAMPUAN KOGNITIF DALAM MENGENAL KONSEP BILANGAN DENGAN PERMAINAN TRADISIONAL DAKON ANAK TK A RA TEAM CENDEKIA KECAMATAN DUKUH PAKIS KOTA SURABAYA - Agustien Lilawati (Universitas Muhammadiyah Gresik, 2020)
The background of this class action research is the ability of children who are lacking in recognizing the concept of numbers. Of the 20 kindergarten students in group A, there were 3 active students in the activity while 17 other children were just silent and experiencing problems. There are 3 active students in the activity while 17 other children are just silent and experience problems from 20 kindergarten students in Group A. This study aims to find out and improve teaching in school and increase the ability to recognize the concept of numbers by using traditional play media media in kindergarten children A RA Team Scholar Surabaya. Research data collection through observation. Research activities are planning and implementation as well as observation and reflection. There are two cycles used in this study, the first cycle and the second cycle. From the research, it was found that the indicator of success level was reached during the second improvement. Indicator of the success rate is only 40% in the first cycle, this means that still not fulfilled the predetermined standard of children's ability achievement of 80%.